Government-Sponsored Health Insurance in India : Are You Covered? - La Forgia, Gerard M. (Directions in development (Washington, D.C.), 2012)
This book presents research findings on India?s major central and state government-sponsored health insurance schemes (GSHISs). The analysis centers on the GSHISs launched since 2007. These schemes targeted poor populations, aiming to provide financial protection against catastrophic health shocks, defined in terms of inpatient care. Focus is on two lines of inquiry. The first involves institutional and?operational? opportunities and challenges regarding schemes? design features, governance arrangements, financial flows, cost-containment mechanisms, underlying stakeholder incentives, informat.